Questions & Answers

Question

Answers

A. 4

B. 6

C. 3

D. 8

Answer
Verified

Given, the radius of a circle is increased by 3 times.

Let us assume that $r$ is the radius of the circle. Then its diameter twice the radius. It is given by,

$d = 2r$… (1)

Now the radius has increased by 3 times. Let the new radius be $r'$. So, we can write,

$r' = 3r$… (2)

Let the new diameter be $d'$. As the diameter is twice the radius, we can write,

$d' = 2r'$

Using equation (2), we get,

$

d' = 2\left( {3r} \right) \\

\Rightarrow d' = 6r \\

$

Now we can apply equation (1)

$ \Rightarrow d' = 3 \times d$

From the above equation, we can conclude that the increased diameter is 3 times the initial diameter. So, if the radius of a circle is increased by 3 times then the diameter is also increased by 3 times.

Hence,